2017
DOI: 10.1039/c6nr06417e
|View full text |Cite
|
Sign up to set email alerts
|

Paper microchip with a graphene-modified silver nano-composite electrode for electrical sensing of microbial pathogens

Abstract: Rapid and sensitive point-of-care diagnostics are of paramount importance for early detection of infectious diseases and timely initiation of treatment. Here, we present cellulose paper and flexible plastic chips with printed graphene-modified silver electrodes as universal point-of-care diagnostic tools for the rapid and sensitive detection of microbial pathogens or nucleic acids through utilizing electrical sensing modality and loop-mediated isothermal amplification (LAMP). We evaluated the ability of the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 77 publications
0
40
0
Order By: Relevance
“…Electrical sensing is a powerful modality that can be used for the development of microfluidic-based platforms for target cells or pathogen sorting and detection (Shafiee et al 2009; Shafiee et al 2010, Shafiee et al 2015, Safavieh et al 2016). Electrical sensing-based methods through impedance magnitude measurement of intact bacteria captured on interdigitated electrodes usually requires high concentration of bacteria on the surface of electrodes in order to generate a detectable electrical sensing (Dastider et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrical sensing is a powerful modality that can be used for the development of microfluidic-based platforms for target cells or pathogen sorting and detection (Shafiee et al 2009; Shafiee et al 2010, Shafiee et al 2015, Safavieh et al 2016). Electrical sensing-based methods through impedance magnitude measurement of intact bacteria captured on interdigitated electrodes usually requires high concentration of bacteria on the surface of electrodes in order to generate a detectable electrical sensing (Dastider et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Among the various sensing modalities used in the development of biosensors for bacteria detection, impedance spectroscopy has shown great promise due to its simplicity, low-cost, portability, and adaptability to multiplexing (Boehm et al 2007; Gibson et al 1992). It has been used in developing biosensors for virus detection as well (Shafiee et al 2013; Shafiee et al 2015; Safavieh et al 2016). The impedance-based sensing mechanisms developed by others are based on the detection of signal changes due to binding target bacteria on the surface of a functionalized electrode.…”
Section: Introductionmentioning
confidence: 99%
“…From our previous studies, 9,30,31 we found that the change in the impedance is maximum at 1 kHz. Additionally, we found a high signal-to-noise ratio for 1 kHz.…”
Section: Methodsmentioning
confidence: 61%
“…They immobilized gold nanoparticles and detect probe conjugates on a nitrocellulose membrane for the LFS layer to capture target amplicons. (G) Integrated paper-based chip for LAMP products detection by electrical conductivity measurement (Safavieh et al, 2017). (Zhu et al, 2020).…”
Section: Detection Methods For Locmentioning
confidence: 99%
“…The pH value change is not obviously caused by the solution condition and small volume. 5G) was used for the electrical conductivity measurement integrated with LAMP for HIV detection (Safavieh et al, 2017). 5F).…”
Section: Detection Methods For Locmentioning
confidence: 99%